Evaluation of sorghum genotypes for variation in canopy temperature and drought tolerance - Mutava, Raymond Ngao (Kansas State University, 2012)
Sorghum (Sorghum bicolor L. Moench) is the fifth most economically important cereal crop grown worldwide and adapted to a wide range of climatic conditions. Drought stress has been ranked as one of the most significant causes of crop yield loss with its effects on yield and yield components. Conservative water use by plants is one of the strategies that can be used as a drought coping mechanism. The slow wilting trait has been associated with conservative water use and has been found in some sorghum genotypes. The purpose of this study was to use canopy temperature to screen for drought tolerance in sorghum, evaluate water use efficiency for slow wilting sorghum genotypes and determine variability in root morphology and response to drought among sorghum genotypes. Canopy temperature studies were conducted under field conditions using infrared (IR) sensors while water use efficiency and root studies were conducted under greenhouse conditions. Our results showed a distinct separation in canopy temperature among genotypes under field conditions at 2:00 pm to 6:00 pm. Midday canopy temperature depression (CTD) was positively correlated to yield (R2 = 0.19) and harvest index (R2 = 0.11). CTD was also stable for all the genotypes during the period from 1:00 pm to 7:00 pm. There was a negative correlation between CTD and crop water stress index (CWSI) (R2 = 0.34) and a positive one between canopy temperature and CWSI (R2 = 0.50). Evaluation of genotypes for water use efficiency revealed significant variability among sorghum genotypes in the amount of water used (10.48 – 13.52 kg) and transpiration efficiency (TE) (2.64 – 7.11 g kg-1) among genotypes. Slow wilting genotypes were high in TE. Rooting depth increased for some genotypes under drought stress with genotype SC1124 recording the largest increase (180%). Total root length for some genotypes increased by 11 – 113% with genotypes SC224 and SC1019 recording the greatest increase. There was a positive correlation between water used and root length (R2 = 0.21). These results show that there is potential for selection of drought tolerance in sorghum and that genotypes with the slow wilting traits are efficient in water use.
Keywords: Canopy temperature; Sorghum; Transpiration efficiency; Drought stress; Root length; Crop water stress index; Agronomy (0285); Plant Sciences (0479)